1986
DOI: 10.1016/s0735-1097(86)80453-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coronary occlusion during percutaneous transluminal angioplasty in humans on left ventricular chamber stiffness and regional diastolic pressure-radius relations

Abstract: The effect of repeated (3 to 10 second) and transient (15 to 75 second) abrupt coronary occlusion on the global and regional chamber stiffness was studied in nine patients undergoing angioplasty of a single proximal left anterior descending coronary artery stenosis. The left ventricular high fidelity pressure and volume relation was obtained before and after the procedure as well as during coronary occlusion, after 20 seconds (n = 9) and after 50 seconds (n = 5). During ischemia, there was an upward shift of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(65 citation statements)
references
References 26 publications
4
60
0
1
Order By: Relevance
“…Previous investigations1 12 have reported that the rate of isovolumic relaxation, reflected by peak negative dP/dt or T, decreases during ischemia, but these investigations have not provided any information on the quantitative aspects of this association. Figure 7 (upper panel) shows that there are two phases to this relation and that the sensitivity of the rate of isovolumic relaxation to reductions in coronary perfusion pressure depends on the pressure achieved.…”
Section: The Rate Of Relaxationmentioning
confidence: 92%
“…Previous investigations1 12 have reported that the rate of isovolumic relaxation, reflected by peak negative dP/dt or T, decreases during ischemia, but these investigations have not provided any information on the quantitative aspects of this association. Figure 7 (upper panel) shows that there are two phases to this relation and that the sensitivity of the rate of isovolumic relaxation to reductions in coronary perfusion pressure depends on the pressure achieved.…”
Section: The Rate Of Relaxationmentioning
confidence: 92%
“…Though abnormal relaxation is the first mechanical manifestation of myocardial ischemia,194, 195, 196 acute coronary artery syndromes seldom precipitate HFpEF decompensation or present as HFpEF 100, 197. The prevalence of CAD ranges from 35% to 53% in large HFpEF registries 34, 35, 198.…”
Section: Cad Phenotypementioning
confidence: 99%
“…Brief coronary occlusions (Ͻ60 seconds) induced at the time of angioplasty have been associated with persistent abnormalities in ventricular compliance. 93 Sheiban et al 94 induced longer periods of coronary artery occlusion (5 to 7 minutes) during angioplasty and observed that recovery of regional wall motion required 24 to 36 hours. Recovery in function was improved with calcium channel blockade.…”
Section: Myocardial Stunning In Humansmentioning
confidence: 99%